Generasi Milenial di Era Digital: Tantangan Finansial, Keterampilan, Gaya Hidup, dan Solusi Berbasis Literasi - Zainal, Zainal; Afrizalmi, Jahimi (Tadabbur: Jurnal Peradaban Islam, 2024)
The millennial generation was born and raised in the digital era, characterized by rapid advancements in information and communication technology. Their close connection with technology brings numerous benefits to daily life but also presents complex challenges. This article aims to analyze the major challenges faced by the millennial generation in the digital era, particularly in the aspects of economy and finance, skills, and lifestyle. This study employs a qualitative approach using a literature review method, in which data are collected from various sources, including books, scientific journals, and relevant research reports. Content analysis is applied to identify patterns, trends, and implications of these challenges. The findings indicate that millennials face significant financial challenges, such as economic instability, difficulties in accessing housing, and consumerism pressures. Additionally, technological advancements require them to acquire new skills, both technical skills and soft skills, such as critical thinking and emotional intelligence. From a lifestyle perspective, the influence of social media has affected consumption patterns and the mental well-being of this generation. In response to these challenges, this study proposes three key strategies: first, enhancing economic and financial literacy. Second, emphasizing the learning process and self-development rather than merely focusing on outcomes. Third, adopting a simple lifestyle that prioritizes needs over desires.